Propuesta de un modelo de gestión de calidad para el hospital Miguel Hilario Alcívar de Bahía de Caráquez - Loor Vergara, Ramona Zoraida (2021)
The main objective of the research work was to propose a quality management model for the Miguel Hilario Alcívar hospital. An inductive, deductive, analytical and synthetic methodology was used. Weighting matrices were developed to assess internal and external factors, subsequently three quality management models were analyzed to determine their adaptability to the needs of the hospital. The main results reflect that: there is no adequate treatment on the part of the administrative and personnel health towards the users, lack of diligence in the needs of the patients, the infrastructure is not its own so it does not have internal accessibility routes or road signs. emergencies, added to the reduced spaces in the waiting room, elements that produce inefficiency in the quality of health services directed to the community. It is concluded that the institution must apply the proposal of the EFQM quality management model since it allows to act in relation to the processes framed by the facilitating agents, results that will be reflected in the people of the institution, in the users and in the community in general.